Hypohidrotic ectodermal dysplasia and atopic dermatitis. - Milano, A. (European Journal of Pediatric Dermatology, 2017)
Because of its high frequency in the pediatric age, atopic dermatitis can be present in any rare infant’s disease and especially in almost all inherited skin disorders. However, in some inherited skin disorder such as hypoidrotic ectodermal dysplasia the association with atopic dermatitis is statistically significant (1, 2). Mark et Al., comparing the incidence of atopic disease in adolescents aged 13 - 14 affected by hypoidotic ectodermal dysplasia with that of adolescents matched for age and sex of the ISAAC study – International Study of Asthma and Allergies in Childhood – showed that in subjects with ectodermal dysplasia the incidence of asthma and allergic rhinitis is double, but that of atopic dermatitis is 5 - 7 times higher. Possible causes are dysgammaglobulinaemia due to NEMO mutations, impaired production of physiological secretions, dietary difficulties and alterations of the skin barrier.